2020
DOI: 10.1007/s43390-020-00148-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of upper extremity function and its relation to curve pattern in female adolescents with idiopathic scoliosis: a pilot study

Abstract: Study design Cross-sectional and clinical measurement.Objective To evaluate upper extremity function and its relation to the curve pattern in idiopathic scoliosis. Summary of background data Postural alterations and trunk distortions-caused by three-dimensional deformity itself in idiopathic scoliosis-may lead to functional changes in the upper extremity of subjects. Methods Handgrip, pulp and lateral pinch strengths, hand dexterity, hand reaction time, coordination of upper extremity, upper extremity performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Recent studies have found that an assessment of grip strength predicts the risk of progression of AIS [13] . Meanwhile, Gozde [14] et al studied upper extremity function and its relationship to type of scoliosis in patients with idiopathic scoliosis, including grip strength, lateral pinch strength, hand dexterity, hand reaction time, upper extremity coordination, upper extremity function, throwing accuracy, and self-reported assessment of upper extremity disability, and found that upper extremity function is affected to varying degrees in patients with scoliosis, especially in patients with scoliosis in whom main thoracic curvature occurs. Adolescents with main lumbar scoliosis tended to have decreased upper extremity function in concave lateral curves compared with adolescents with main thoracic scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that an assessment of grip strength predicts the risk of progression of AIS [13] . Meanwhile, Gozde [14] et al studied upper extremity function and its relationship to type of scoliosis in patients with idiopathic scoliosis, including grip strength, lateral pinch strength, hand dexterity, hand reaction time, upper extremity coordination, upper extremity function, throwing accuracy, and self-reported assessment of upper extremity disability, and found that upper extremity function is affected to varying degrees in patients with scoliosis, especially in patients with scoliosis in whom main thoracic curvature occurs. Adolescents with main lumbar scoliosis tended to have decreased upper extremity function in concave lateral curves compared with adolescents with main thoracic scoliosis.…”
Section: Discussionmentioning
confidence: 99%